Pyrene/coumarine-subphthalocyanine conjugates as light harvesting systems with intramolecular energy transfer. (December 2020) - Lioret, Vivian; Rousselin, Yoann; Decréau, Richard A.
Abstract: A series of subphthalocyanine-antenna dyads have been successfully designed, synthetized and characterized by 1 H NMR, 13 C NMR, high-resolution mass spectroscopy and X-ray diffraction for some of them. Pyrene and coumarine have been appended at the axial position of the subphthalocyanine scaffold using different types of linkers. Photophysical properties of the new compounds have been measured in toluene, tetrahydrofuran, chloroform, dimethyl sulfoxide and methanol. Energy transfer efficiencies between antenna and the subphthalocyanine platform have been investigated and almost quantitative energy transfer occurs in the antenna-platform 5 . Graphical abstract: Image 1 Highlights: The Energy Transfer Efficiency was studied in four new subphthalocyanine-fluorophore conjugates. Pyrene and coumarine were used as antenna in the subphthalocyanine-containing dyad. Different linkers were used to append the antenna at the axial position of the subphthalocyanine.